PERANAN MEDIATOR DALAM MEMEDIASI PERKARA PERCERAIAN - Bustamam Usman (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2018)
Marriage is a bond of inner birth between a man and a woman who is expected to create a sense of sakinah, mawaddah warahmah. To achieve this, it is necessary for both of them to have mutual understanding and mutual understanding of the interests of both parties, especially those relating to rights and obligations, in domestic life we often encounter husbands and wives complaining and complaining to others or their families, due to non-fulfillment the rights that must be obtained or not carried out by one of the parties, or for other reasons that can result in a dispute between the two husband and wife, so a mediation is needed to resolve the problem. It is not impossible that the dispute will lead to a break in marriage (divorce).